Detection of discretized single-shell penetration in mesoscopic vortex matter - Dolz, M. I.; Fasano, Y.; Cejas Bolecek, N. R.; Pastoriza, H.; Konczykowski, M.; van der Beek, C. J.; Fasano, Yanina (IOP Publishing, 2014)
Fil: Fasano, Y. Comisión Nacional de Energía Atómica. Instituto Balseiro. Laboratorio de Bajas Temperaturas; Argentina